The Pengaruh Dimensi Service Quality Terhadap Customer Loyalty Yang Dimediasi Oleh Customer Satisfaction Toko Ritel Alfamat Di Kota Cimahi - Santoso, Muhammad Catur Ibnu; V. Santi Paramita (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to analyze the influence of service quality dimensions on customer loyalty, mediated by customer satisfaction at the Alfamart retail store in Cimahi City. The method used in this research is quantitative with an associative descriptive approach. The population in this study were men and women over 17 years old, domiciled in Cimahi City, and had shopped at Alfamart in Cimahi City. The sampling technique used in this research was convenience sampling with a non-probability sampling method with a sample size of 140 sample. The type of data collected is qualitative data, quantified into quantitative data, and the data source in the research is primary data originating from respondents. This research shows that the service quality dimensions, namely assurance and empathy, positively affect customer loyalty, both directly and through customer satisfaction. Meanwhile, the other dimensions, tangible, reliability, and responsiveness, do not directly or indirectly influence customer satisfaction. With these results, it is hoped that they can provide suggestions and input to managers to increase assurance and empathy by looking at the indicators that form these dimensions.